REMOTE SITE MIKROTIK VPN DENGAN POINT TO POINT TUNNELING PROTOCOL (PPTP) STUDI KASUS PADA YAYASAN TERATAI GLOBAL JAKARTA - Elly Mufida; Dedi Irawan; Giatika Chrisnawati (Universitas Bumigora, 2017)
Technology VPN (Virtual Private Network) allows everyone to be able to access the local network from outside by using the internet. Through the VPN, the user can access the resources within the local network, gain rights and settings are the same as physically being in a place where the local network is located. Data security and secrecy of data transmission from unauthorized access in transmission on the Internet becomes the main standard in the VPN, so that the VPN is always included will be the main feature is the encryption and tunneling.